Psychosocial Vulnerability of Children Due to Exposure to Extreme Weather: A Systematic Literature Review - Achmad Rizki Azhari; Osep Yasier Almunsiri; Nur Afifah Harahap (Universitas Pahlawan Tuanku Tambusai, 2025)
According to UNICEF, by 2050, an estimated 2.2 billion children will face the direct impacts of global warming, with heat stress identified as a key consequence. This article presents a global systematic literature review examining the psychosocial vulnerability of children exposed to extreme weather. Using a qualitative descriptive approach, relevant studies were identified through searches on ResearchGate, Google Scholar, and PubMed. The review focused on publications from 2020 to 2025 and ultimately included eight studies that met the inclusion criteria. A total of 62 articles were initially screened. The findings reveal that exposure to high temperatures significantly increases the risk of mental health issues in children, such as stress, sleep disturbances, depressive episodes, and post-traumatic stress disorder. These psychosocial effects highlight the urgent need to enhance the resilience of vulnerable children and their families, enabling them not only to cope with the effects of climate change but also to adapt to evolving environmental conditions. Strengthening social and emotional support systems is essential to mitigate the long-term psychological impact of climate-induced extreme weather on younger populations.